Women and Onion Farming in Lakor Island, Southwest Maluku Regency - Sopamena, Junianita Fridianova (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Up to this day, research on women-related topics has not completely revealed the independent contribution of women towards household income. This research’s aim was to analyze the existence of women’ contributions to their household income through onion farming on Lakor Island. The research data was chosen deliberately of 30 women who did onion farming in Werwawan Village, Lakor Island. The data collection was done by intense interview techniques and data confirmation to the related parties such as instructors and sellers. The data obtained through direct involvement of researchers using a list of questions, as well as direct observation to the women's activities in onion farming as a reflection of a qualitative approach. The results showed that most of the women engaged in onions farming independently, by utilizing home yards until open a land with an area of 1-2 hectares. The onion farming activities, contributed around Rp. 1,500,000 - 2,500,000 per planting season without assistance from men (husband). The contribution of women to household income reaches 60-80 percent. Therefore, women play an important role in improving the household economy through their contribution to household income.